Maslahah Mursalah: A Substantial Effort to Overcome Income and Wealth Inequality in Indonesia - Tholkhatul Khoir; Eman Sulaiman (Universitas Islam Negeri Raden Mas Said Surakarta, 2024)
Income and wealth inequality in Indonesia persists despite efforts by central and local governments to address it. maslahah mursalah provides a strong theoretical foundation for creating policies that are both religious and highly beneficial. This study aims to explain the history of using maslahah mursalahin income and wealth policies, provide evidence of income and wealth inequality in Indonesia, and explore the potential of using maslahah mursalah to address this inequality. This study examines two key facts: the history of maslahah mursalah's policies on income and wealth, and income and wealth inequality in Indonesia. They were obtained from Arabic usul al-fiqhliterature and the analysis of the Gini ratio and palm index. The data were compared to determine the most urgent policy needs and thepossibility of using maslahah mursalah as the basis. This study found that maslahah mursalahhas been widely used in income and wealth distribution policies. Since income and wealth inequality in Indonesia still exists and continues to increase in the ratio, maslahah mursalah willlikely be the basis of settlement policy. This study aims to provide a robust theoretical foundation for the Indonesian government to design and implement maslahah mursalah-based policies to address income and wealth inequality, including human capital development, labour market opening for women, labour rights protection, improved access to finance, social transfer programs, zakat and tax optimisation, housing policy reform, and increased transparency and corruption eradication.